Efficacy of MgSO4 to prevent eclampsia in women with severe pre-eclampsia and impending eclampsia - Kollu, Bhuvana Shanti; Talathi, Manju Arvind; Taralekar, Vaishali Suhas (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Preeclampsia is a multi-system disorder that is frequently accompanied by proteinuria and new-onset hypertension. Poor placental perfusion and a general disease process that may affect multiple organ systems are the hallmarks of the syndrome. While eclampsia is a complicated condition brought on by cerebral dysrhythmia due to various pathogenesis steps that include abnormal trophoblastic invasion which led to vasospasm, endothelial dysfunction, and platelet aggregation. Maternal complications of severe preeclampsia/eclampsia can lead to maternal, fetal, and neonatal morbidity and mortality. One of the anticonvulsants MgSO4 is known to reduce the risk of eclampsia. The present study was conducted with the aim to analyse the effect of MgSO4 to reduce the incidence of eclampsia in pregnant women with preeclampsia and impending eclampsia. Methods: A total of 114 women with preeclampsia and impending eclampsia were included in present study. Mgso4 was given as a loading dose and the Zuspan regimen as required. Women were categorised based on raised blood pressure (>140/90 mmHg), deranged lab parameters which includes renal function tests (urea, uric acid, creatinine), coagulation profile (PT, APTT, INR, LDH, platelet count), liver function tests (total bilirubin, SGOT/SGPT) and clinical symptoms which include headache, blurring of vision, epigastric pain. The incidence of eclampsia even after a dose of MgSO4 was calculated. Results: The mean age of the women was 28.17±4.69 years. The diagnosis of pre-eclampsia was made based on systolic and diastolic blood pressure. Out of 114 pregnant women with severe preeclampsia or impending eclampsia who were given a dose of MgSO4, only 2 women have developed eclampsia. Conclusions: The incidence of eclampsia after the dose of MgSO4 among women with preeclampsia or impending eclampsia was reported to be only 1.75% which confirms MgSO4 therapy as an effective tool in preventing perinatal morbidity and mortality.